Colour as motion graphic element in early awareness campaign towards colour blind in Malaysia / Siti Nornadzahirah Roslanm and Sharkawi Che Din - Roslanm, Siti Nornadzahirah; Che Din, Sharkawi (Universiti Teknologi MARA, 2020)
Colour is an element seen by humans, and the colour is an element that gives emotion and mood to someone who sees it, if a person cannot see the colours around them, they are someone who has colour blindness problems. If not detected from the beginning, the effects of this colour blindness problem will result in various disorders on their health, especially on their emotions. Colour blindness is one of the diseases that not many people are aware of its existence. Therefore, this study has three main objectives that will help this study to produce an early awareness campaign towards colour blindness more effectively. The first objective is, to study the percentage of Malaysians with colour blindness, second, to identify appropriate and effective colours in motion graphics against colour blind people, and third, to produce an early awareness campaign toward colour blindness problems in motion graphics with colour seen by colour blind people. Furthermore, this study will use primary and secondary methods, the first method is observation and the second method is an online survey, these two methods will be used to collect data more accurately based on the study conducted. Besides this study will also involve the selected target audience, which is parents from Nadi Sarjana kindergarten and colour blind people. This research will produce an early awareness campaign towards colour blindness problems in motion graphics by using colours seen by colour blind people for more effectiveness in this campaign. In conclusion, the researchers hope that the campaign will be able to convey the message more effectively to the public.